Integrating Internet in Teaching and Learning EFL: The Case Study of First-Year English Students at Sidi Bel Abbès University - Ghouraf, Khadidja (جامعة الجزائر2 - أبو القاسم سعدالله, 2022)
من خلال هذه الدراسة، نحاول أن نستعرض استعمال ودمج الإنترنت في تعليم وتعلم اللغة الإنجليزية كلغة أجنبية ونهدف بذلك إلى تحديد دورها وتأثيرها على العمليتين في الجامعة الجزائرية. لجمع البيانات من عينة طلبة ومدرسي اللغة الإنجليزية بجامعة جلالي ليابس بسيدي بلعباس التي طبقت عليها الدراسة، ارتأينا أن نطبق منهجية متعددة الوسائل بما فيها من استبيانات، حوارات، محافظ ورقية وأخرى إلكترونية. بينت النتائج أن للشبكة العنكبوتية دور فعال في جعل الطلاب أكثر استقلالية، اهتماما بتعلم اللغة الإنجليزية وكذا أكثر اعتمادا على أنفسهم. من جانب آخر، استخدامها في التدريس يوطد التحصيل بفضل الأدوات والوسائط الأصلية التي توفرها. يتطرق المقال أيضا إلى عرض بعض التوصيات بخصوص استعمال الإنترنت بغرض تدريس وتعلم اللغة الإنجليزية كلغة أجنبية. It is not a surprising fact that the prevalence of Internet use in language education nowadays has brought novelty to the field like never before. The present paper pinpoints its integration in teaching and learning EFL (English as a Foreign Language) and aims at investigating its role and impact on those processes at the Algerian university. A mixed-methods approach was applied to gather relevant data from a sample of students and teachers at Djillali Liabès University in Sidi Bel Abbès; using students’ questionnaires, portfolios and e-portfolios besides teachers’ interviews. The results showed that Internet plays a key role in increasing learner centeredness and makes students more autonomous and interested in learning EFL in addition, its incorporation to teaching does consolidate the language course, for it provides authentic and innovative materials and tools. The paper presents as well some future recommendations about Internet use in teaching and learning EFL.
Keywords: جامعة سيدي بلعباس -- التعليم الإلكتروني -- اللغة الإنجليزية -- طلبة الجامعة